Aflatoxins: Finding solutions for improved food safety - Unnevehr, Laurian J.; Grace, Delia (International Food Policy Research Institute, 2013)
A key tenet of the CGIAR Research Program on Agriculture for Nutrition and Health (A4NH) is that agricultural practices, interventions, and policies can be better configured both to maximize health and nutrition benefits and to reduce health risks. This is particularly true regarding aflatoxins and other mycotoxins, an important food safety health risk with significant implications for developing countries.